A unified approach for determining the strength of Frc members subjected to torsion—Part I: Experimental investigation. (14th October 2021) - Facconi, Luca; Amin, Ali; Minelli, Fausto; Plizzari, Giovanni
Abstract: The strength and behavior of fiber reinforced concrete (FRC) members subjected to torsion has received little attention in the literature. The primary objective of including fibers in concrete is to bridge cracks once they form, and in doing so, provide some post‐cracking resistance to the otherwise brittle concrete. This and the accompanying paper that follows present the results of a comprehensive experimental and analytical study aimed at describing the behavior and strength of FRC members subjected to torsion. In this paper, results are presented on large scale pure torsion tests which have been conducted on eighteen 2.7 m long by 0.3 m wide by 0.3 m high beams with varying transverse and longitudinal reinforcement ratios along with varying steel fiber types and dosages. The results of this study demonstrates that the addition of steel fibers significantly increases the stiffness, rigidity and the maximum resisting torque and maximum twist when compared to the same specimen without fibers. The addition of fibers substantially reduced crack widths and crack spacings induced by torsion. The complementary behavior of specimens containing fibers and stirrups is explored along with a critical discussion on members containing low amounts of conventional longitudinal and/or transverse reinforcement.